Intestinal antiviral signaling is controlled by autophagy gene Epg5 independent of the microbiota. Issue 5 (4th May 2022) - Lee, Sanghyun; Kalugotla, Gowri; Ingle, Harshad; Rodgers, Rachel; Wu, Chunyan; Wang, Yating; Li, Yuhao; Yang, Xia; Zhang, Jin; Borella, Nicolette R.; Deng, Hongju; Droit, Lindsay; et al.
ABSTRACT: Mutations in the macroautophagy/autophagy gene EPG5 are responsible for Vici syndrome, a human genetic disease characterized by combined immunodeficiency. Previously, we found that epg5 −/- mice exhibit hyperinflammation in the lungs mediated by IL1B/IL-1β and TNF/TNFα, resulting in resistance to influenza. Here, we find that disruption of Epg5 results in protection against multiple enteric viruses including norovirus and rotavirus. Gene expression analysis reveals IFNL/IFN-λ responsive genes as a key alteration. Further, mice lacking Epg5 exhibit substantial alterations of the intestinal microbiota. Surprisingly, germ-free mouse studies indicate Epg5- associated inflammation of both the intestine and lung is microbiota-independent. Genetic studies support IFNL signaling as the primary mediator of resistance to enteric viruses, but not of microbial dysbiosis, in epg5 −/- mice. This study unveils an important role, unexpectedly independent of the microbiota, for autophagy gene Epg5 in host organism protection by modulating intestinal IFNL responses. Abbreviations: CTNNB1: catenin (cadherin associated protein), beta 1; DAPI: 4′, 6-diamidino-2-phenylindole; EPG5: ectopic P-granules autophagy protein 5 homolog (C. elegans); FT: fecal transplant; IFI44: interferon-induced protein 44; IFIT1: interferon-induced protein with tetratricopeptide repeats 1; IFNG/IFN-γ: interferon gamma; IFNL/IFN-λ: interferon lambda; IFNLR1: interferon lambda receptor 1; IL1B/IL-1β: interleukin 1 beta; ISG: interferon stimulated gene; GF: germ-free; LEfSe: linear discriminant analysis effect size; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MNoV: murine norovirus; MX2: MX dynamin-like GTPase 2; OAS1A: 2'-5' oligoadenylate synthetase 1A; RV: rotavirus; SPF: specific-pathogen free; SQSTM1/p62: sequestosome 1; STAT1: signal transducer and activator of transcription 1; STING1: stimulator of interferon response cGAMP interactor 1; TBK1: TANK-binding kinase 1; TNF/TNFα: tumor necrosis factor